Evaluasi Penerapan Sistem Manajemen Mutu ISO 9001:2015 pada PT. X dengan Metode Analisa Gap - Richard Susanto (Jurnal Titra, 2022)
PT. X is a company that produces coolbox, bioaga, and road barriers. In order to maintain the company's performance and product quality, PT. X has a quality management system, namely ISO 9001:2015. But in fact PT. X still has not implemented a good quality management system. This can pose a risk to the company's performance and product quality that can be disrupted. Therefore, this research was conducted to knowing the level of conformity of the implementation of the quality management system with the actual conditions in PT. X and provide suggestions for improvements. This study identified 5 findings of problems that exist in the implementation of the company's quality management system that are not in accordance with the ISO 9001:2015 standard. Then an analysis is carried out to find out the root cause of the problem using the fishbone diagram and five whys analysis method. From the results of the analysis of the root causes of the problem then a proposed improvement is designed to be able to resolve the problem findings by referring to the clauses in the ISO 9001:2015 document. The results of this study are expected to be used and can be useful for PT. X.